Transformation of diatom Phaeodactylum tricornutum by electroporation and establishment of inducible selection marker. (June 2012) - Niu, Ying-Fang; Yang, Zhi-Kai; Zhang, Meng-Han; Zhu, Cong-Cong; Yang, Wei-Dong; Liu, Jie-Sheng; Li, Hong-Ye
Diatoms are important primary producers in the marine ecosystem. Currently it is difficult to genetically transform diatoms due to the technical limitations of existing methods. The promoter/terminator of the nitrate reductase gene of the model diatom Phaeodactylum tricornutum was cloned and used to drive chloramphenicol acetyltransferase (CAT) reporter gene expression. The construct was transferred by electroporation into P. tricornutum grown in medium lacking silicon. CAT expression was induced in transformed diatoms in the presence of nitrate, enabling growth in selective medium, and was repressed when ammonium was the only nitrogen source. Expression of CAT transcript and protein were demonstrated by RT-PCR and Western blot analysis, respectively. Our study is the first to report a successful genetic transformation of diatom by electroporation in an economical and efficient manner and provides a tightly regulated inducible gene expression system for diatom.